Freedom and the contractual perspective from the discourse of political modernity to the discourse of contemporary liberalism (Study in Contractualism OF John Locke and the evolution of Contractualism BY John Rawls) (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This research deals with the perceptions of the classical and contemporary contractual philosophers about the issue of political freedom, and how the development of the related to the limits of political freedom and its characteristics and its relationship to the modern state, society and the individual, through the models of John Locke and John Rawls. The research notes the development of the formula of the social contract From theory of the social contract and its formula affected on the development of these perceptions the modernist stage to the contemporary stage through the transformation of the social contract formula of John Rawls into a mathematical theoretical assumption, that deals with a typical political setuation through (Original Position) argument, which discusses the choices of individuals in a state of uncertainty and withholding information, which imposes on individuals a position that requires careful rationality , restricting freedom in this imaginary model position of rational choice, while leading to guaranteeing freedoms and the possibility of developing them in the case of concluding the social contract agreement represented by Rawls’ principles of justice, Rawls’ formula is an actual development of John Locke’s contractuality, but with the exclusion of the natural state from the basic assumption, and the restoration of Immanuel Kant's moral theories, and their reinforcement through the idea of ​​duty, which was missing in John Locke's contractual theory, which represents an agreement that limits the random, excessive, and not guaranteed freedom that exists in the state of nature, and it is the same as Hobbes’ assumption that assumes harshly the human aggression.  Despite the agreement of the two classic and contemporary contracts in the end, we can notice that the basic assumption led to a change in the function of the social contract with regard to freedom, while remaining a guarantor of it in both cases.